The influence of service employees' nonverbal communication on customer-employee rapport in the service encounter. (20th March 2017) - Lin, Cheng-Yu; Lin, Jiun-Sheng Chris
Abstract : Purpose: Rapport between service employees and customers has been suggested to be an important determinant of customer relationship management, yet existing marketing literature still lacks a sufficient understanding of how service employees' nonverbal communication affects customer-employee rapport development in service encounters. The purpose of this paper is to fill this research gap by proposing and testing a model that explores how service employees' nonverbal communication (employee affective delivery and behavioral mimicry) influences customer positive emotions and customer-employee rapport. The mediating role of customer positive emotions and the moderating role of store atmosphere in the process of customer-employee rapport development were also assessed. Design/methodology/approach: Using an observational methodology in conjunction with a customer survey, multi-source survey data collected from 303 customer-employee pairs in the apparel retailing industry was examined through structural equation modeling and regression analysis. Findings: Results showed that employee nonverbal communication positively influenced customer positive emotions and customer-employee rapport. The partial mediating role of customer positive emotions and the moderating role of store atmosphere in the process of rapport development were also confirmed. Practical implications: Service firms should train and motivate employees to use nonverbal communication to develop and strengthen customer-employee rapport. The importance of customer positive emotions in the service process should be addressed in the customer-employee rapport development process. Moreover, service managers should also allocate firm resources to create a well-designed store atmosphere for target customers. Originality/value: This research represents one of the earliest studies to explore and empirically test the influence of employee nonverbal communication on customer-employee rapport development in service encounters. The partial mediating role of customer positive emotions and the moderating role of store atmosphere on the relationship between employee nonverbal communication and customer-employee rapport were also proposed and confirmed.